The Role of CTHRC1 in Regulation of Multiple Signaling and Tumor Progression and Metastasis - Dan Mei; Yue Zhu; Lingling Zhang; Wei Wei (Mediators of Inflammation)
Collagen triple helix repeat containing-1 (CTHRC1) has been identified as cancer-related protein. CTHRC1 expresses mainly in adventitial fibroblasts and neointimal smooth muscle cells of balloon-injured vessels and promotes cell migration and tissue repair in response to injury. CTHRC1 plays a pivotal role in some pathophysiological processes, including increasing bone mass, preventing myelination, and reversing collagen synthesis in many tumor cells. The ascended expression of CTHRC1 is related to tumorigenesis, proliferation, invasion, and metastasis in various human malignancies, including gastric cancer, pancreatic cancer, hepatocellular carcinoma, keloid, breast cancer, colorectal cancer, epithelial ovarian cancer, esophageal squamous cell carcinoma, cervical cancer, non-small-cell lung carcinoma, and melanoma. And molecules that regulate the expression of CTHRC1 include miRNAs, lncRNAs, WAIF1, and DPAGT1. Many reports have pointed that CTHRC1 could exert different effects through several signaling pathways such as TGF-β, Wnt, integrin β/FAK, Src/FAK, MEK/ERK, PI3K/AKT/ERK, HIF-1α, and PKC-δ/ERK signaling pathways. As a participant in tissue remodeling or immune response, CTHRC1 may promote early-stage cancer. Several recent studies have identified CTHRC1 as an effectual prognostic biomarker for predicting tumor recurrence or metastasis. It is worth noting that CTHRC1 has different cellular localization and mechanisms of action in different cells and different microenvironments. In this article, we focus on the advances in the signaling pathways mediated by CTHRC1 in tumors.